Preparation, High-Density Spherical, and Low Sensitivity of RDX/NC/PMMA Composite Particles. (18th October 2021) - Jia, Xinlei; Peng, Wenshan; Xu, Lanjuan; Cao, Qing; Xing, Shaohua; Liu, Guangyi; Geng, Xiaoheng; Guo, Haiying; Han, Guojun; Wang, Jingyu
Abstract : In order to reduce the mechanical sensitivity of cyclotrimethylenetrinitramine (RDX) and improve its energy density, spherical RDX/PMMA/NC composite particles were prepared by spray drying method, selecting polymethyl methacrylate (PMMA, hydrocarbon binder) with excellent mechanical properties and nitrocellulose (NC, energy-containing binder) with higher density as the desensitizing shell material, RDX as the core material. PMMA/NC composite particles of the same component were prepared by a simple solvent evaporation method at the same time. Structural characterizations and thermal stability of the composites were systematically studied by scanning electron microscopy (SEM), X-ray diffraction (XRD), and differential scanning calorimeter (DSC), respectively. Moreover, the safety performance has been qualitatively tested and analyzed through impact sensitivity and friction sensitivity. The results show that the addition of NC/PMMA binder would not change the original crystal structure of RDX, and the RDX/NC/PMMA composites fabricated by spray drying presented spherical particles with uniform distribution and smooth surface. The Tp0 of RDX/NC/PMMA composite particles increased from 220.3°C to 228.2°C, improving the thermal decomposition performance. The H50 rose from 29.32 cm to 84.3 cm, and the probability of friction explosion decreased from 96% to 8%, significantly enhancing the safety performance. In short, the RDX/NC/PMMA composites prepared via the spray drying method and the improvement of their performance have positive significance for the development of explosives in pursuit of high energy and low sensitivity.